Les enfants des autres = Other people's children [videorecording (DVD)] - Zlotowski, Rebecca; Efira, Virginie, 1977-; Zem, Roschdy; Mastroianni, Chiara, 1972-; Ferreira-Goncalves, Callie; Couture, Yamée; Tabary, Henri-Noël; Lefebvre, Victor; Pouderoux, Sébastien, 1982-; Wiseman, Frederick (Music Box Films, 2023)
Rachel is a dedicated teacher who forms a deep bond with her boyfriend's young daughter, loving the family she's found but yearning for one of her own in this soulful, sexy, resolutely grown-up story of the elusive quest for belonging.